Korelasi Antara Living Law dan Asas Legalitas dalam Konteks Pembaharuan Hukum Pidana Nasional Berdasarkan KUHP 2023 - Berliana Aisyah Nur Salwa; Tongat Tongat (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The reform of Indonesia’s criminal law through Law Number 1 of 2023 concerning the Criminal Code (KUHP) marks a fundamental shift in the national criminal justice system, particularly through the formal recognition of the living law as law that lives within society. This article analyzes the correlation between living law and the principle of legality within the context of national criminal law reform. The study employs a normative juridical method with statutory, conceptual, and comparative approaches to examine how the 2023 Criminal Code seeks to balance legal certainty with substantive justice. The findings indicate that the regulation of the principle of legality in Article 1 of the KUHP remains the primary foundation for ensuring the protection of individual rights and preventing arbitrary state actions. However, the recognition of living law under Article 2 of the KUHP expands the sources of criminal law beyond written statutes to include social values living within the community, insofar as they are consistent with Pancasila, general legal principles, and human rights. The relationship between the principle of legality and living law in the 2023 KUHP is not antagonistic but rather complementary and harmonious. Living law enriches the legality principle substantively through moral and social justice dimensions, while the legality principle serves as a normative safeguard to maintain legal certainty and prevent the abuse of power. Therefore, the integration of both principles reflects a new paradigm of Indonesian criminal law that is pluralistic, just, and civilized, reaffirming the nation’s legal politics grounded in Pancasila values and the principles of a democratic rule of law.